Expression Patterns of TNFα, MAdCAM1, and STAT3 in Intestinal and Skin Manifestations of Inflammatory Bowel Disease. (21st December 2017) - Vavricka, Stephan R; Galván, Jose A; Dawson, Heather; Soltermann, Alex; Biedermann, Luc; Scharl, Michael; Schoepfer, Alain M; Rogler, Gerhard; Prinz Vavricka, Mareike B; Terracciano, Luigi; Navarini, Alexander; Zlobec, Inti; et al.
Abstract: Background: Pathogenesis of cutaneous extraintestinal manifestations [EIM] in inflammatory bowel disease [IBD] remains elusive. Efficacy of anti-TNF agents suggests TNF-dependent mechanisms. The role of other biologics, such as anti-integrins or JAK-inhibitors, is not yet clear. Methods: We performed immunohistochemistry for TNFα, NFκB, STAT1/STAT3, MAdCAM1, CD20/68, caspase 3/9, IFNγ, and Hsp-27/70 on 240 intestinal [55 controls, 185 IBD] and 64 skin biopsies [11 controls, 18 erythema nodosum [EN], 13 pyoderma gangenosum [PG], 22 psoriasis]. A semiquantitative score [0–100%] was used for evaluation. Results: TNFα was upregulated in intestinal biopsies from active Crohn`s disease [CD] vs controls [36.2 vs 12.1, p < 0.001], but not ulcerative colitis [UC: 17.9]. NFκB, however, was upregulated in intestinal biopsies from both active CD and UC [43.2 and 34.5 vs 21.8, p < 0.001 and p = 0.017, respectively]. TNFα and NFκB were overexpressed in skin biopsies from EN, PG, and psoriasis. No MAdCAM1 overexpression was seen in skin tissues, whereas it was upregulated in active UC vs controls [57.5 vs 35.4, p = 0.003]. STAT3 was overexpressed in the intestinal mucosa of active and non-active IBD, and a similar upregulation was seen in skin biopsies from EN [84.7 vs 22.3, p < 0.001] and PG [60.5 vs 22.3, p = 0.011], but not in psoriasis. Caspase 3 and CD68 overexpression in skin biopsies distinguished EN/PG from psoriasis and controls. Conclusions: Upregulation of TNFα/NFκB in EN and PG is compatible with the efficacy of anti-TNF in EIM management. Data on overexpressed STAT3, but not MAdCAM1, support a rationale for JAK-inhibitors in EN and PG, while questioning the role of vedolizumab.